Revealing The Correlation between Students’ Grammatical Competence and Speaking Performance - Hanafi, Moh; Septiana, Ayu Rizki (Universitas Pahlawan Tuanku Tambusai, 2024)
Grammatical competence and speaking performance are interrelated components of language proficiency. Developing both aspects requires a balanced approach to language instruction that integrates grammar learning with speaking practice. This research is intended to investigate the correlation between students’ grammatical competence and their speaking performance. There were 19 students who were taken as the sample of this study. To take the data, grammar test and speaking test were administered. The result showed that the grammar test of the students was 79.86 in average or B+. Meanwhile, the speaking test resulted on 73.47 in average or it can be categorized into B. Further, the test of Pearson Correlation Product moment revealed that the coefficient of the correlation was .468 which was at moderate positive correlation. In addition, the significance of the correlation resulted on 0.043. Since it is lower than the level of significance 0.05, it can be concluded that H0 is rejected. It means that there is a significant correlation on students’ grammatical competence and their speaking performance.